Pemberdayaan Masyarakat Pada Program Keluarga Harapan (PKH) - Handayani, Linda; Aliyudin, Aliyudin (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
The PKH program is a program that is quite effective and can be felt directly by the community in order to save the nation’s next generation, namely through education and health. This study aims to determine community empowerment in the Family Hope Program (PKH), how the process of empowering the micro (individual) level, how the process of empowering the mezzo (group) level, and the process of empowering the macro (mass) level. This research uses a descriptive method. The results showed that community empowerment in the Family Hope Program (PKH) in Kadudampit District was going well because it was seen from the participation of the community in the health or education sector, so that the Family Hope Program provided many significant changes and improvements to the community in their daily lives both in the economic, education and health sectors.